Male infertility and human environmental pollution - Kołłątaj, Witold; Kołłątaj, Barbara; Karwat, Dorota Irena; Klatka, Maria; Kozyra, Katarzyna (Journal of Education, Health and Sport, 2017)
Introduction. Man is the only being that has created an artificial environment, or civilization. The development of civilization entails changes in the environment. The rapid growth of the impact of human economic activity has led to such changes that are able to threaten not only other living creatures but also themselves. Increasing environmental pollution are well-known factors negative influencing on human environment. Is now a global problem. Anthropogenic pollution contribute to the unfavorable demographic changes and grooving number of health problems of the population. Unfavourable demographic changes manifest themselves as not only increment in the number of deaths and malformations (defects in the reproductive organs), but also as decrement in the fertility rates being the consequence of increasing the growing problem of couples infertility. There is observed the increasing role of male factor in the couple infertility problem. In some developed countries its participation rate reaches 50%. Objective. The aim of the study is to assess the impact of environmental pollution on human development and reproductive function of male gonads. Material and methods. The study was carried out using the method of data analysis published in the works and scientific reports. Current state of knowledge. The paper presents information on identified environmental pollution with proven adverse effects on the development of the gonads and the their reproductive function. There are also known possible negative impacts of environmental pollution on carcinogenesis in male gonads. Wider awareness of the negative impact of environmental pollution and attempts put emphasis on primary prevention can give better long-term effects than increasing spending on the therapies of developmental disorders as well as gonadal dysfunctions symptoms including fertility problems. Conclusions. Among the environmental pollutants there are many chemicals adversely affecting the organogenesis as well as reproductive function of testicles. Many of these contaminants are pesticides or chemicals currently approved for use in agriculture and industry, including the food and cosmetics industry. Those chemicals, adversely affecting organogenesis and testicular generative function, are present in air, water and foods, packaged foods and everyday objects - including clothes (ingredients sponges), perfumes, creams and detergents. The increase in environmental pollution coincides with the deterioration of sperm quality and reduction in male infertility in highly civilized countries. Striving for continuous reduction of the environmental seems to be necessary to stop the growing problem of couples infertility.